Exploration of Politeness Strategies Between Main Characters in the Green Book Movie - Mustofa, Ihyak; Fadhilah, Nurul; Zain, Abdul Rahman; Nasrullah, Nasrullah (Journal of Language Intelligence and Culture, 2024)
This study aims to analyze Brown and Levinson's language politeness strategies in the conversation between Dr. Shirley and Tony Lip in the film Green Book. The approach used in this research is descriptive qualitative, using document analysis as the method of analysis. The data analysis process was conducted through four stages: data collection, data reduction, data presentation, and conclusion drawing. The results of the data analysis revealed some significant findings. First, Dr. Shirley tends to use politeness strategies more frequently than Tony Lip, comparing 43 uses by Dr. Shirley and 25 by Tony Lip. Second, the positive face politeness strategy is the dominant strategy both main characters use. Third, several factors influence politeness strategies, including power, social distance, personality differences, and social culture.